Study of Two Layered Immiscible Fluids Flow in a Channel with Obstacle by Using Lattice Boltzmann RK Color Gradient Model - Salaheddine Channouf; Youssef Admi; Mohammed Jami; Mohammed Amine Moussaoui (International Journal of Renewable Energy Development, 2023)
Lattice Boltzmann method (LBM) is employed in the current work to simulate two-phase flows of immiscible fluids over a square obstacle in a 2D computational domain using the Rothman-Keller color gradient model. This model is based on the multiphase Rothman-Keller description, it is used to separate two fluids in flow and to assess its efficacy when treating two fluids in flow over a square obstacle with the objective of reducing turbulence by adjusting the viscosities of the two fluids. This turbulence can cause major problems such as interface tracking techniques in gas-liquid flow and upward or downward co-current flows in pipes. So, the purpose of the study is to replace a single fluid with two fluids of different viscosities by varying these viscosities in order to reduce or completely eliminate the turbulence. The results show that to have stable, parallel and non-overlapping flows behind the obstacle, it is necessary that the difference between the viscosities of the fluids be significant. Also, showing that the increase in the viscosity ratio decreases the time corresponding to the disappearance of the vortices behind the obstacle. The results presented in this work have some general conclusions: For M≥2, the increase in the viscosity difference leads to an increasing of friction between fluids, reducing of average velocity of flow and decreasing the time corresponding to the disappearance of the vortices behind the obstacle. However, for M≤1/2, the opposite occurs.